The continuum of care as a unifying framework for intergenerational and interspecies health equity - Craig Stephen; Chris Walzer; Chris Walzer (Frontiers Media S.A., 2023)
IntroductionUnlocking the full potential of different people and organizations to address existential health threats requires shared goals and frameworks that allow people to see themselves contributing to a common and shared continuum of care. A new narrative to help people implement collective action for collective problems is needed.MethodsThis paper is draw from the co-authors experience working from the local to international level on planetary health problems.ResultsThe proposed conceptual framework expands the socioecological model of health to help formulate multilevel approaches that foster healthier circumstances for all by revealing the mutual benefits that emerge from pooling expertise, funding, and political will to solve multiple problems with coordinated investment of resources and effort. It is intended to support program planning and communication. This framework is a response to the absence of systematic attempts to concurrently counteract the social and environmental conditions leading to disease, dysfunction and deficits which is increasingly seen as being problematic, especially as the root causes of health problems and solutions converge across species, sectors, and generations. The framework is embedded in the idea of interspecies and intergenerational health equity.DiscussionEnsuring interspecies and intergenerational health equity requires each actor to fulfill their roles along the continuum while supporting the needs of others. A socio-ecological continuum of care provides bundled options that combine knowledge from different sectors, disciplines and perspectives to guide interventions over time across a comprehensive array of services and support spanning all levels of needs, species and generations.